Isolation of astaxanthin from marine yeast and study of its pharmacological activity - Ushakumari, Uma Nath; Ramanujan, Ravi (International Current Pharmaceutical Journal, 2013)
The aim of the present study was to isolate and study about the antibacterial activity of astaxanthin from marine yeast. Astaxanthin a carotenoid present in marine yeast and crustaceans posses a wide range of pharmacological activity. Yeast strain was isolated from the marine sediments collected from Cochin, Kerala during the month of August 2012. The samples were collected in sterile plastic covers and brought to the laboratory without exposing to the external environment further. The marine sediment samples were directly inoculated in yeast malt. After effective screening the strains containing astaxanthin was refrigerated for further use. The strains were purified by TLC using petroleum hexane: acetone (3:1). A spectrophotometric assay was carried out by measuring absorbance at 200-500nm. The antibacterial activity was studied on several organisms like Bacillus Subtilis, Salmonella typhi, Staphylococcus aureus and Pseudomonas aeroginosa. The extracts showed excellent antibacterial activity than the standard chloramphenicol. Among this, Pseudomonas aeroginasa showed maximum inhibition. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13584 International Current Pharmaceutical Journal, February 2013, 2(3): 67-69